Central Corneal Thickness: Ultrasound Pachymetry Verus Anterior Segment Optical Coherence Tomography: Doi: 10.36351/pjo.v37i4.1260 - Ali, Waqas; Shakir, Munira; Wasim, Sahira; Afza, Ronak (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the mean difference in central corneal thickness between ultrasound pachymetry and anterior segment optical coherence tomography in patients visiting tertiary care hospital of Karachi Study design: Cross sectional study Place and Duration of Study: Department of Ophthalmology, Liaquat National Hospital, Karachi from 27th December 2018 to 26th June 2019. Methods: Total 216 eyes of 108 patients were divided into two groups. Central corneal thickness was measured using ultrasound pachymeters in group A and with anterior segment optical coherence tomography in group B. Data was collected and analyzed using SPSS version 21. Mean central corneal thickness was compared between the two methods. Stratification was done on gender, age and post-stratification independent sample t-test was applied for mean difference CCT and P-value ? 0.05 was taken as significant. Results: Total 108 patients were equally divided into two groups. Mean age was 48.70±7.82 years in group A and 50.66±6.88 years in group B. In group A, there were 74.1% males and 25.9% females while in group B, there were 75.9% males and 24.1% females. There was statistically significant difference between the mean central corneal thickness of group A and group B for right and left eyes (p<0.001). Mean difference was also compared for gender and age groups. We found statistically significant differences in central corneal thickness in between the two methods in both age groups (?45 years and > 45 years). Conclusion: Central corneal thickness was more with pachymeters as compared to the AS-OCT (p value < 0.05) Key Words: Central Corneal Thickness, Anterior Segment Optical Coherence Tomography, Ultrasound Pachymetry.